Reassembly of plural and human features in the L2 acquisition of Chinese by adult Korean speakers. (October 2019) - Su, Jiajia
This article reports on a study investigating the second language (L2) acquisition of the plural and human features in Mandarin Chinese by adult Korean speakers. Both plural and human features are represented in Korean and Chinese, but assembled in different ways. Forty-eight L2 learners at beginner, intermediate, and advanced Chinese proficiency levels and twenty-three native speakers of Chinese were tested using a grammaticality judgment task. The results show that L2 learners can successfully reassemble the two features, though L2 specific contexts and restrictions on feature realization are difficult. The advanced group has achieved native-like performance. The findings provide empirical evidence for the Feature Reassembly Hypothesis (Lardiere, 2009).